The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.30880/jtet.2020.12.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A Problem-Solving Flipped Classroom Module: Developing Problem-solving Skills among Culinary Arts Students

Abstract: Problem-solving skills areimportant at the workplacein Culinary Arts for initiating innovative andcreative solutions. However, graduates from community colleges in Malaysia seem to haveonlyaverage level of problem-solving skills, while instructors do not seem to emphasise developing problem-solving skillswhen conducting lessons. Hence, providing more opportunities in solving real-world problems forwork is required. AFlipped Classroom approachbeginswith activities conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, to develop students’ abilities to solve the problem of food waste in practice, it is also necessary to train them to face the problems encountered in practice logically and efficiently and come up with creative solutions that can reduce food waste based on the observed food waste problems (e.g. how to use surplus food materials for other purposes) (Techanamurthy et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, to develop students’ abilities to solve the problem of food waste in practice, it is also necessary to train them to face the problems encountered in practice logically and efficiently and come up with creative solutions that can reduce food waste based on the observed food waste problems (e.g. how to use surplus food materials for other purposes) (Techanamurthy et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The study of Techanamurthy et al (2020) on teaching students culinary skills via problem solutions found that the flipped teaching model could not only solve practical problems but also increase students' creativity in solving the problem of food waste.…”
Section: School Sustainability Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile apps can reduce costs and enhance the learning experience by providing immediate feedback. Furthermore, all businesses including education have been affected by the Internet of Things, Artificial Intelligence (AI), and automation, which has resulted in a shift in employee skill requirements (Techanamurthy et al, 2020). Hill and his colleagues (2015) developed hybrid learning modules in response to the increasing volume of information for students to absorb and the expanding variety of students, which has put a demand on practitioners to discover other ways of teaching science topics.…”
Section: Integrating Technology Within Hybrid Learningmentioning
confidence: 99%
“… Tien et al (2020) believe that the traditional approaches to teaching hospitality technology courses cause students to only learn via one-way cramming, meaning they are less innovative and lack creative ability as well as a basic understanding of the principles and operating parameters of hospitality technology. Techanamurthy et al (2020) also believe that hospitality technology courses focus on the teaching of technology and the theory of apprenticeship, while traditional courses do not emphasize the ability to solve problems. Therefore, Chandra et al (2022) believed that in traditional distance teaching, hospitality technology courses are more difficult to teach through one-way communication, and that they should only be used as supplementary teaching materials.…”
Section: Literaturementioning
confidence: 99%